Phylogenetic interrelationships of living and extinct Tinamidae, volant palaeognathous birds from the New World - Bertelli, Sara Beatriz (2014)
Tinamous, one of the earliest diverging living avian lineages, consists of a Neotropical clade of palaeognathous birds with a fossil record limited to the early Miocene–Quaternary of southern South America. Here, we conduct a comprehensive, morphology-based phylogenetic study of the interrelationships among extinct and living species of tinamous. Morphological data of fossil species are included in a matrix of 157 osteological and myological characters of 56 terminal taxa. The monophyly of most recognized genera is supported by the results of the analysis. The cladistic analysis also recovers the traditional subdivision between those tinamous specialized for open areas (Nothurinae) and those inhabiting forested environments (Tinaminae). Temporal calibration of the resultant phylogeny indicates that such a basal divergence had already taken place in the early Miocene, some 17 million years ago. The placement of the fossil species within the open-area (Nothurinae) and the forest-dwelling (Tinaminae) tinamous is also consistent with the palaeoenvironmental conditions inferred from the associated fauna.